2019
DOI: 10.3390/coatings9090570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deposition Pressure on the Microstructure and Optical Band Gap of Molybdenum Disulfide Films Prepared by Magnetron Sputtering

Abstract: MoS2 films were prepared via magnetron sputtering under different deposition pressures, and the effects of deposition pressure on the crystal structure, surface morphology, and optical properties of the resulting films were investigated. The results show that the crystallinity of the films first increases and then decreases with increasing pressure. The surface of the films prepared by magnetron sputtering is dense and uniform with few defects. The deposition pressure affects the grain size, surface morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Figure 4a,b illustrates the total spectrum of the Cu 3 N/MoS 2 heterojunction and MoS 2 thin film, respectively. Figure 4a depicts that the binding energies of the S2p, Mo 3d, N1s, O1s, and Cu2p peaks were 162.6, 227.8, 397.4, 530.5, and 931.3 eV, respectively [15]. Figure 4b shows that the S2p and Mo 3d peaks appeared at the binding energies of 161.5 and 229.5 eV, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 4a,b illustrates the total spectrum of the Cu 3 N/MoS 2 heterojunction and MoS 2 thin film, respectively. Figure 4a depicts that the binding energies of the S2p, Mo 3d, N1s, O1s, and Cu2p peaks were 162.6, 227.8, 397.4, 530.5, and 931.3 eV, respectively [15]. Figure 4b shows that the S2p and Mo 3d peaks appeared at the binding energies of 161.5 and 229.5 eV, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Among these heterojunctions, Cu 3 N/MoS 2 shows promise as a photocatalyst because Cu 3 N is an outstanding semiconductor material that can substantially enhance the photoelectric performance of MoS 2 or introduce new functions into such heterojunctions. As a typical transition metal sulfide, MoS 2 has a S-Mo-S sandwich structure combined by the van der Waals force [14,15]. Given its unique structure and photoelectric properties, MoS 2 has attracted considerable attention from scholars [16,17] and has been widely investigated for thin film transistors [18,19], photodetectors [20,21], and solid lubrication [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the effects of sputtering power [9,10], sputtering pressure [11], and incident flux angles [12] on the synthesis of molybdenum disulfide films by magnetron sputtering have been reported, and the influence of sputtering temperature on the frictional properties of molybdenum disulfide films have also been discussed [13,14]. The effect of RF power variation on film thickness as well as resistivity was investigated by Park [9] et al As the RF power increases, the film thickness increases from 100 nm to 240 nm, and its resistivity increases from 356 to 2006 Ω/sq.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al [10] found that the change in RF power 2 of 11 has a significant effect on the binding energy of Mo atoms. Gong et al [11] suggested that the huge discrepancy in electronegativity between MoS 2 molecules promotes film defects at different deposition pressures, which in turn causes changes in the bandgap. They also pointed out that the optimal pressure for sputtering is 1.0 Pa. Li et al [12] continued to investigate the effect of incident angular flux on molybdenum disulfide films deposited by magnetron sputtering and found that the structure of MoS 2 films changed significantly with the variation of incident angular flux.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, there are few reports on Cu 3 N and MoS 2 composite films. MoS 2 is a typical layered 2D material, in which Mo and S are covalently bonded, and layers are connected by van der Waals force [42][43][44][45]. As the number of layers increases, the band gap also varies, and the band gap width gradually changes from 1.29 eV to 1.80 eV [43,[46][47][48][49].…”
mentioning
confidence: 99%